History with or without the Sparkle – Gloss in the Margin of the Next Discussion - Šmahel, František (Dějiny – teorie – kritika, 2010)
The development of art studies research, superb books presenting the artistic heritage and in particular huge exhibitions with many visitors are beginning to find an unintended response in broad historical public awareness. This particularly involves artistic artefacts from the Luxembourg era which as pars pro toto have taken on the role of history-making agent. For the basic line to stand out properly it needed a contrast, i.e. Hussitism as a new Dark Ages, when instead of the likes of Hus and Chelčický iconoclasts and destroyers of sacred buildings came to the fore. What was at best only indirectly indicated in specialist works became fodder for cheap journalism.